2021
DOI: 10.1099/jgv.0.001574
|View full text |Cite
|
Sign up to set email alerts
|

The green tea catechin epigallocatechin gallate inhibits SARS-CoV-2 infection

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has caused a pandemic with tens of millions of cases and more than a million deaths. The infection causes COVID-19, a disease of the respiratory system of divergent severity. No treatment exists. Epigallocatechin-3-gallate (EGCG), the major component of green tea, has several beneficial properties, including antiviral activities. Therefore, we examined whether EGCG has antiviral activity against SARS-CoV-2. EGCG blocked not only the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 50 publications
7
107
0
Order By: Relevance
“…CoVs[23], was inhibited by EGCG treatment. Interestingly, EGCG was recently shown to significantly inhibit authentic SARS-CoV-2 infection, and time-of-addition experiments suggested that EGCG at least partially blocks SARS-CoV-2 entry[25], consistent with our findings. In this study, we expand the scope of EGCG activity to other CoVs, including murine and bat CoVs, and demonstrate the physiological relevance of the inhibitory activity of EGCG on CoV attachment and infection of lung epithelial cells.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…CoVs[23], was inhibited by EGCG treatment. Interestingly, EGCG was recently shown to significantly inhibit authentic SARS-CoV-2 infection, and time-of-addition experiments suggested that EGCG at least partially blocks SARS-CoV-2 entry[25], consistent with our findings. In this study, we expand the scope of EGCG activity to other CoVs, including murine and bat CoVs, and demonstrate the physiological relevance of the inhibitory activity of EGCG on CoV attachment and infection of lung epithelial cells.…”
supporting
confidence: 91%
“…Finally, recent studies have identified in vitro inhibitory effects of EGCG against the SARS-CoV-2 3C-like protease [3437]. However, our time-of-addition experiments with HCoV-229E and HCoV-OC43, as well as those of others with SARS-CoV-2 [25], strongly suggest that EGCG predominantly inhibits authentic CoV infection by blocking entry, although other activities might be exerted at higher concentrations. Furthermore, we show that EGCG reduces cell surface binding of HCoV-OC43 and VSV-SARS-CoV-2, in a similar manner to heparin, which has been demonstrated to competitively block virion attachment [11].…”
Section: Discussionmentioning
confidence: 65%
“…Despite several limitations, the findings of present study might help to elucidate on the mechanisms of action of the anti-viral effects of catechins in the oral cavity. Recent studies reported an inhibitory effect of EGCG on COVID-19, which has increased attention toward green tea as a non-pharmacological preventive measure [ 19 , 20 , 21 ]. Although there are still many unknowns regarding the clinical effects of catechins in humans, we believe that the results of this study will guide future research related to catechins and contribute to their further development toward enhancing human health.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG), an active constituent of green tea, has been identified as a potential inhibitor of the RBD domain and other proteins of SARS-CoV-2[ 37 ]. The effect of green tea consumption may be explored for inhibition of S protein domains to prevent its binding with ACE2[ 38 ]. This may be particularly effective in the gastrointestinal tract, as the oral route implies maximum availability in the digestive tract.…”
Section: Mechanisms Of Gastrointestinal Tract Involvementmentioning
confidence: 99%